1974
DOI: 10.1101/sqb.1974.039.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of an RNA Primer for Initiation of Rous Sarcoma Virus DNA Synthesis In Vitro

Abstract: An early, obligatory step in replication of RNA tumor viruses is transcription of the genetic information of the virion RNA genome into DNA. This DNA is then integrated as the provirus into the DNA of the host cell (Temin 1964(Temin , 1971 Varmus et al., this volume). Like all DNA polymerases studied so far, the virion-associated RNA-directed DNA polymerase of Rous sarcoma virus (RSV) requires a nucleic acid primer molecule to initiate synthesis (Fliigel and Wells 1972;Verma et al. 1972;Taylor et al. 1973; F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Among those 4 S RNA species bound to the 60-70 S RNA is one which serves as a primer for RNA-dependent DNA synthesis in vitro (Canaani and Duesberg, 1972). Its structure has been determined; it is identical to a cellular tryptophan transfer RNA species and shows specific binding affinity to RNA-dependent DNA polymerase Dahlberg et al, 1974Dahlberg et al, , 1975Panet et al, 1975b). This 4 S RNA species is the only low molecular weight RNA species in the virion for which a function is known.…”
Section: The Virion Contains Cellular and Viral Rnamentioning
confidence: 96%
“…Among those 4 S RNA species bound to the 60-70 S RNA is one which serves as a primer for RNA-dependent DNA synthesis in vitro (Canaani and Duesberg, 1972). Its structure has been determined; it is identical to a cellular tryptophan transfer RNA species and shows specific binding affinity to RNA-dependent DNA polymerase Dahlberg et al, 1974Dahlberg et al, , 1975Panet et al, 1975b). This 4 S RNA species is the only low molecular weight RNA species in the virion for which a function is known.…”
Section: The Virion Contains Cellular and Viral Rnamentioning
confidence: 96%
“…yeast tRNATrp, and the sequences of tRNAsTrp from beef and chicken are alike [22,22]. Chicken tRNATrp is known to be a primer for reverse transcriptase from avian myeloblastosis virus 1221 ; moreover, reverse transcriptase forms in vitro a complex with chicken and beef tRNAsTrP [23-251. Therefore, one may presume that tryptophanyl-tRNA synthetase and reverse transcriptase possess some regions of their structure in common.…”
Section: Irnmunochemical Comparison O J Tryptophanyl-trna Synthetasesmentioning
confidence: 99%
“…Yeast tRNATrP differs in structure from primer tRNATrp [22,26] in the region of nucleotides complementary to viral RNA [27], and cannot serve as a primer. It was of interest to elucidate whether yeast tRNAT'p can bind to reverse transcriptase.…”
Section: Irnmunochemical Comparison O J Tryptophanyl-trna Synthetasesmentioning
confidence: 99%
“…It is generally accepted that all these RNAs are incorporated passively into the virions at the time of 'budding', and thus may have no special function. However, more recently, it has been shown that the synthesis of cDNA from 70-S RNA by reverse transcriptase uses an RNA primer which has been identified as tryptophan-tRNA in the avian system [7,8].In the course of an investigation designed to identify the RNA priming the transcription of the murine oncornavirus genome by reverse transcriptase, the presence in acrylamide gels of a band representing a new species of RNA was noted as a constant finding. This species of RNA, which we will refer to as 5.9-S RNA, is found in murine oncornaviruses, and also in cell lines, both virus-producing and non-producing.…”
mentioning
confidence: 99%
“…It is generally accepted that all these RNAs are incorporated passively into the virions at the time of 'budding', and thus may have no special function. However, more recently, it has been shown that the synthesis of cDNA from 70-S RNA by reverse transcriptase uses an RNA primer which has been identified as tryptophan-tRNA in the avian system [7,8].…”
mentioning
confidence: 99%